Toxocara (Nematoda: Ascaridida) and Other Soil-Transmitted Helminth Eggs Contaminating Soils in Selected Urban and Rural Areas in the Philippines - Vachel Gay V. Paller; Emmanuel Ryan C. de Chavez (The Scientific World Journal)
The extent of contamination of soils with soil transmitted helminthes (STH) eggs, particularly Toxocara, was determined in selected urban and rural towns of Laguna, Philippines. Soil samples were collected from public schools, house yards, and empty lots. Results revealed that, of the 1480 soil samples collected, 460 (31%) were positive for STH eggs. Toxocara sp. was the most prevalent (77%), followed by Ascaris sp. (11%), hookworms/strongyles/free-living nematodes (7%), and Trichuris sp. (5%). Some soil physicochemical parameters were also determined and associated with Toxocara eggs prevalence and density in soil. Results revealed that Toxocara sp. eggs were most prevalent in less acidic, relatively high temperature and high moisture soil conditions. They were also prevalent in sandy, silty, and loamy soil textures but less prevalent in clayey. No significant differences were found between depth 1 (0–5 cm) and depth 2 (6–10 cm). This study revealed that Toxocara sp. eggs are ubiquitous and the extent of contamination in soils from the selected towns of Laguna is relatively high. Hence, the data generated in this study can be used in promoting public awareness, particularly for pet owners and local health officials, for effective prevention and control of this parasitosis.